The Use of Herbal Medicines in Pregnancy: A Cross-sectional Analytic Study - Onwusulu Nnaemeka; Nnamani Phyllis; Offor Chinaza (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Background and aim: The use of complementary and alternative medicine is increasing worldwide; Some of the medications, including native herbs, are taken just before conception and in all trimesters and may be risky to the conceptus. The extent and the factors affecting usage vary and have not been adequately studied. The study aimed to determine the prevalence and factors associated with Herbal medicine use among pregnant and recently pregnant women. Materials and methods: Magnitude of use of Herbal medication, the sociodemographic, other associated factors and, the various types of the medications used were evaluated. It was a cross-sectional study. An unvalidated semi-structured, interviewer-assisted questionnaire was used to obtain information. Consenting current or recently pregnant women attending public tertiary and private specialist hospitals were included in the study, while unconscious, severely sick women were excluded; 120 responded and were consecutively recruited. Stata version13 statistical software was used for data analysis. The prevalence, type of Herbal medicines used, associated factors, and pregnancy outcomes were measured. A two-sided (5% significance level) test of significance at a 95% confidence level was adopted. The study duration was three months, from October to December 2020. Results: The rate of usage of Herbal medication in the index pregnancy was 22.5%; bitter leaf was the highest 6 (22.2%), followed by Herbal concoctions (agbo) and moringa- 18.5% and 11.1%, respectively. Malaria in pregnancy was the commonest indication (18.5%). Usage was lower amongst high parity patients; use is the same across sociodemographic strata. Family and friends were the primary sources of information (40.7%). Conclusion: The use of natural or Herbal products in pregnancy was relatively common in the study. The medications were used mainly for the presumed diagnosis of malaria. Therefore, there is a need for health personnel to be actively involved in the education of pregnant women, especially in the early trimester and lower parity, about Herbal drug use and the inherent dangers.